HUMAN IMMUNODEFICIENCY VIRUS (HIV): A DIAGNOSTIC DILEMMA - Rathore, Muhammad Ali; Niazi, Saifullah Khan; Rathore, Mommana Ali; Yazdani, Muhammad Sajid (Pakistan Armed Forces Medical Journal, 2022)
Human immunodeficiency virus is a blood borne virus and is being routinely screened in the blood banks since 1983. The sensitivity and specificity of HIV tests have improved dramatically over the years, but even then, false positive results do occur, which need confirmatory testing. A young male who arrived at Armed Forces Institute of Transfusion (AFIT), Rawalpindi, for blood donation, was repeatedly “positive” on serological assays. Nucleic acid amplification test (NAT) was performed which gave a “Negative” result. Line immunoassay (LIA) was performed to solve the discrepancy in test results.